2015
DOI: 10.21608/jpp.2015.49782
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sunflower Cultivated in Sandy Soils at a Wide Range of Planting Dates in Egypt

Abstract: In Egypt, newly reclaimed soils offer a great opportunity to increase the area devoted to oilseed crops. The objectives of this research were to determine the optimum planting date(s) that achieve the highest seed and oil yields per unit land area and to determine the suitable cultivar for sandy soils of Wadi El-Natroon region, Egypt. As well as, study the changes in fatty acid profile entire year. The field experiments were conducted in the Desert Exp. Sta. Fac. Agric., Cairo Univ., Wadi El-Natroon, El-Beheir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
2
6
1
Order By: Relevance
“…1). These results are not in full agreement with those of Hamza & Safina (2015), who reported a reduction in oil percentage from 38.5 to 37%, due to delay in sowing date.…”
Section: Sowing Date Effectcontrasting
confidence: 99%
See 2 more Smart Citations
“…1). These results are not in full agreement with those of Hamza & Safina (2015), who reported a reduction in oil percentage from 38.5 to 37%, due to delay in sowing date.…”
Section: Sowing Date Effectcontrasting
confidence: 99%
“…Similarly, Abd El Mohsen ( 2012), observed that seed yield of the cultivars Sakha 53, Giza 102 and the hybrid Pioneer 63M02 was reduced from 2.32, 1.96 and 1.89ton/ ha when sown on the 1 st of May to 1.58, 1.23 and 1.14 t/ha when sown on the 1 st of July, respectively. Moreover, Hamza & Safina (2015) indicated that the delay in sowing from March (where maximum seed yield and oil yield were obtained) to August, resulted in average reduction in seed yield for the two cultivars Sakha 53 and Giza 102 from 2.49ton/ ha to 1.90ton/ha, respectively. Means followed by the same letter within the same column are insignificantly different at 0.05 level of probability.…”
Section: Sowing Date Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in accordance with our study results, indicating that under Ukrainian conditions, sunflower is quite sensitive to edaphic and climatic factors, which can explain from 34 to 58% of the variations in the parameters of the crop yield dynamics. It should be noted that sunflowers are adaptable to a wide variety of soils and are even successfully cultivated on sandy soils (Hamza and Safina, 2015), nevertheless, the crop gives the best results on good soils suitable for growing corn or wheat (Radanielson et al, 2012). Our study confirmed that sunflower yields positively correlated with the SOC, which directly reflects soil fertility.…”
Section: Soil Determinants Of Sunflower Yieldssupporting
confidence: 75%
“…Numerous researchers have found significant positive correlations between morphological characters such as head diameter and seed yield (HLADNI et al, 2003;KAYA et al, 2009;HLADNI et al, 2010;DARVISHYADEH et al, 2011;ŠKORIĆ, 2012;HAMZA and SAFINA, 2015).…”
Section: Introductionmentioning
confidence: 99%